ANALISIS UPAYA MENINGKATKAN STRATA AKREDITASI PARIPURNA PUSKESMAS MATANGA KABUPATEN BANGGAI LAUT - Samsudin, Sultan; Nurfaizah, Sitti; Togubu, Diana Mirja (Bina Generasi : Jurnal Kesehatan, 2025)
As one method to optimize the quality of health services is by accreditation assessment. This study aims to analyze efforts to improve the plenary accreditation strata of the matanga health center of the Banggai Laut district.This research method uses qualitative research with a descriptive approach, with a total of five informants, the selection of informants is determined by purposive sampling technique. Data collection was obtained through interviews and observations. Data analysis was carried out qualitatively. The results showed that the head of the health center has a very important role in making accreditation decisions, it needs to be prepared as well as possible both from the budget, facilities and infrastructure and the readiness of existing resources, organizing according to specified procedures, continuous supervision, implementing continuous monitoring and evaluation and the Planing Do Study Act cycle carried out at the health center to be a measure of service quality. The conclusion of this study is the need for a careful plan in the accreditation process, the implementation of a comprehensive health center management cycle, increasing resources, and improving service quality oriented towards customer satisfaction and quality standardization.